PERFORMANCE ANALYSIS COMPARISON OF COCA COLA AND PEPSI - The, Glenny Marselia; Saerang, David Paul Elia; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2014)
All companies fight to get as many consumers as they can and it makes, product, price, place and promotion become important factors to make a company has a successful marketing campaign. The companies spend much money for create an attractive product at an affordable price, a place that can be reached, and the promotion that can be well-received by the public. So, regarding that fact, the researcher writes a study about the performance analysis comparison of Coca Cola and Pepsi in Manado by using Coca Cola and Pepsi marketing mix(product, price, place, and promotion).The researcher analyzes data based on primary data and secondary data by using SPSS software while, primary data is collected by distributing questionnaires to 100 Manado people. Secondary data is collected by reading various books and browsing the internet. The researcher uses Semantic differential scale. Which shows that coca cola has superior from the product, price, place and promotion compared with Pepsi. Finally, the researcher recommends Coca Cola Company to keep maintaining the advantages, while Pepsi has to make changes to further develop the marketing process. Keywords: performance ,product, price, place, promotion